An Analysis of the Factors that Determine the Foreign Exchange Rate for USD/GBP (Cable) - Li, Fulei (2014)
The following study focuses on the connection between ten nominated factors and high frequent transaction currency, using the USD/GBP rate. These ten factors were taken from Parity approach, Balance of payments approach, monetary approach, Assets approach, and macroeconomic variants intricately related to Cable. The examination range went through financial crisis between 2008 and 2013, according to the above ten variables with Cable. Through multivariate regression and VIF, the impact on Cable can be understood, along with multicollinearity amongst factors. A crucially negative connection exists between the cross exchange rate (EUR/GBP) and Cable (USD/GBP). Furthermore, CPI, inflation rate differential, balance of payment, and assets approaches showed a poor negative connection with Cable, which is against the hypotheses of this time. The remaining variables were lessened by multiple external factors, for which there could not be a clear and important connection found. Keywords: exchange rate; Cable; Multivariate regression; relationship; multicollinearity.